Sosialisasi Kelembagaan Posyandu Remaja Dan Literasi PKHS Sebagai Strategi Preventif Mengurangi Angka Stunting - Almanan, Oesman Raliby; As’ad, Hafizh; Setiawan, Ridwan; Ikhsandi, Iqbal Farihu (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
Stunting remains a significant and critical problem in various geographical areas, so it needs to be continuously discussed, especially in Magelang Regency. The need to reduce stunting has reached a higher urgency, especially in relation to the goals set by the Sustainable Development Goals (SDGs), which is to reduce the incidence of stunting by 40% by 2025. Therefore, the aim of this initiative is to instruct the community in adopting health-promoting behaviors and implementing clean and hygienic living practices in their daily lives to reduce the prevalence of stunting. In this regard, Participatory Rural Assessment is the most effective methodology to explore solutions to the stunting dilemma. In the course of this initiative, there was a marked increase in the existing Posyandu cadres, which encouraged sustainable development. Furthermore, the effort catalyzed the establishment of the Youth Posyandu institution, which functions as a promotive and preventive action against stunting. With the establishment of the Youth Posyandu, various activities related to the posyandu are ready to grow sustainably, because the next generation has been adequately prepared.